2005
DOI: 10.1016/j.jacc.2004.10.057
|View full text |Cite
|
Sign up to set email alerts
|

Serial analyses of N-terminal pro-B-type natriuretic peptide in patients with non–ST-segment elevation acute coronary syndromes

Abstract: The initial rise of NT-proBNP in NSTEACS is mainly reversible. Factors associated with less reversibility are related to chronically impaired left ventricular function, and factors associated with greater reversibility are related to the acute myocardial damage. The NT-proBNP level measured during a chronic, relatively stable phase is a better predictor of mortality than during an acute unstable phase. The clinical setting and timing of measurement will be important to consider when using NT-proBNP for risk as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
3
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 35 publications
3
79
3
2
Order By: Relevance
“…Hess et al (2005b) suggested that in the elderly population, a cut-off level of 125 pg/ml (14.75 pmol/L; 1 pg/ml = 0.118 pmol/L) is useful either to exclude cardiac dysfunction in symptomatic individuals or to risk stratify elderly individuals in terms of the necessity for intervention. Thus, our subjects were classified into these groups according to their NT-proBNP levels, and there was higher number of patients (> 70.0% of all examinees) in group 2 (levels of NT-proBNP higher than 14.75 pmol/L) as expected, since it was shown in earlier studies that patients with NSTE-ACS have elevated levels of NTproBNP (Sabatine et al, 2002;Lindahl et al, 2005;Jernberg et al, 2004;Heeschen and Hamm, 2004). It was also suggested that the NT-proBNP level increases with the level of symptoms as assessed by New York Heart Association (NYHA) classification and the level of impaired left ventricular dysfunction as assessed by echocardiography (Bay et al, 2003;Pfister et al, 2004;Hess et al, 2005a;Drewniak et al, 2008;Kaski et al, 2010).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Hess et al (2005b) suggested that in the elderly population, a cut-off level of 125 pg/ml (14.75 pmol/L; 1 pg/ml = 0.118 pmol/L) is useful either to exclude cardiac dysfunction in symptomatic individuals or to risk stratify elderly individuals in terms of the necessity for intervention. Thus, our subjects were classified into these groups according to their NT-proBNP levels, and there was higher number of patients (> 70.0% of all examinees) in group 2 (levels of NT-proBNP higher than 14.75 pmol/L) as expected, since it was shown in earlier studies that patients with NSTE-ACS have elevated levels of NTproBNP (Sabatine et al, 2002;Lindahl et al, 2005;Jernberg et al, 2004;Heeschen and Hamm, 2004). It was also suggested that the NT-proBNP level increases with the level of symptoms as assessed by New York Heart Association (NYHA) classification and the level of impaired left ventricular dysfunction as assessed by echocardiography (Bay et al, 2003;Pfister et al, 2004;Hess et al, 2005a;Drewniak et al, 2008;Kaski et al, 2010).…”
Section: Discussionmentioning
confidence: 63%
“…Levels of NT-proBNP showed downward trend over time (months) in some other studies (Gill et al, 2004;Eggers et al, 2009). Lindahl et al (2005) took patients' blood samples at baseline, day 2, 6 weeks, 3 months, and 6 months, and NT-proBNP levels were found to decrease throughout the whole sampling period, rapidly in the early phase followed by a more gradual decline.…”
Section: Levels Of Acs Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Akut koroner sendromlu hastalarda NT-pro-BNP düzeylerinin başlangıçtaki hızlı azalmadan sonra en az 6 ay boyunca azalmaya devam ettiği gösterilmiştir. Akut miyokart enfarktüs sonrası takip eden süreçte NT-pro-BNP düzeylerindeki düşmenin daha yavaş olmasının, sol ventrikül sistolik fonksiyonundaki kronik bozulmayla ilişkili olduğu öne sürülmüştür (20). Kardiyak resenkronizasyon tedavisi yapılan hastalarda, NT-pro-BNP düzeylerinin erkenden azalmaya başlaması ve bu azalmanın devam etmesinin, tedavinin etkinliğini yansıtabileceği bildirilmiştir (21).…”
Section: Discussionunclassified
“…However, the natriuretic peptides might also rise in response to a number of other stimuli, among them ischemia per se and cytokines [30,31]. BNP and NT-proBNP have received widespread use for diagnosis of heart failure and evaluation of acute dyspnea.…”
Section: The B-type Natriuretic Peptidementioning
confidence: 99%